Stainless Steel Construction for Palm Sap Filtration Using the Buchner Method - Tuturoong, Nancy Jeane; Robot, Jimmy Reagen; Rondonuwu, Jenny; Mononutu, Edmond C. (International Journal of Contemporary Sciences (IJCS), 2024)
Palm sap, the primary raw material for palm sugar and other derivative products, often faces quality issues due to the presence of solid particles, dirt, and microorganisms that accelerate fermentation and spoilage. This study aimed to design and construct a stainless steel filtration device based on the Buchner method to enhance the cleanliness and quality of palm sap. The filtration system employs a vacuum mechanism to expedite the separation of solid impurities, improving efficiency over conventional gravity methods. Laboratory-scale testing evaluated filtration capacity, clarity, and process time efficiency. Results demonstrated that the device significantly increased sap clarity while reducing filtration time. Additionally, the stainless steel construction proved easy to clean and durable for repeated use. This innovation benefits traditional Minahasa farmers in North Sulawesi, enabling them to produce higher-quality palm sugar. The filtration process effectively reduced dust and water content while increasing sugar concentration to 21.3 Brix without requiring extensive cooking. The use of the Buchner method and SS304 stainless steel construction ensures consistent filtration quality, offering a practical solution to improve palm sap processing and enhance farmers' incomes.